2023
DOI: 10.4103/jfmpc.jfmpc_2301_22
|View full text |Cite
|
Sign up to set email alerts
|

Problem of headache: A cross-sectional study

Abstract: Objectives: To assess the medical students, interns, general practitioners, and family physicians’ perception of neurological and otolaryngeal causes of headaches. Materials and Methods: A prospective, qualitative, questionnaire-based cross-sectional study took place. Five hundred and seventy-one senior medical students, interns, general practitioners (GPs), and family physicians from different geographical regions in Saudi Arabia were involved in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Poor migraine awareness among patients and physicians and gaps in critical knowledge among physicians and medical students have been found to be an issue in some countries, which could be a contributing factor to migraine being misdiagnosed [ 24 27 ]. A recent survey conducted across KSA found that less than half of senior medical students, medical interns, general practitioners, and family physicians had good awareness and knowledge of headache [ 28 ]. Multiple consultations with primary and secondary care physicians left one patient with the impression that many healthcare professionals consider migraine to be ‘just another headache’ and so do not take it seriously.…”
Section: Barriers To Diagnosismentioning
confidence: 99%
“…Poor migraine awareness among patients and physicians and gaps in critical knowledge among physicians and medical students have been found to be an issue in some countries, which could be a contributing factor to migraine being misdiagnosed [ 24 27 ]. A recent survey conducted across KSA found that less than half of senior medical students, medical interns, general practitioners, and family physicians had good awareness and knowledge of headache [ 28 ]. Multiple consultations with primary and secondary care physicians left one patient with the impression that many healthcare professionals consider migraine to be ‘just another headache’ and so do not take it seriously.…”
Section: Barriers To Diagnosismentioning
confidence: 99%